2022
DOI: 10.34117/bjdv8n2-206
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de uma nova metodologia para o ensino de discentes surdos / Application of a new methodology for the teaching of deaf students

Abstract: RESUMOCom o avanço da pandemia do novo coronavírus, houve a migração das escolas para um contexto remoto, no qual o uso das Tecnologias Digitais de Informação e Comunicação (TDICs) passou a ser contínuo. Sendo observado, no presente estudo, que esse atípico cenário mundial manifestou a urgência de abordagens alusivas ao ramo da Educação Ambiental (EA). Entretanto, no setor educacional, existe ainda uma grande carência na produção de ferramentas digitais que se fundamentam nos ideais da inclusão escolar para o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%